Generalized Information for the γ-Order Normal Distribution - Thomas L. Toulias (Journal of Probability and Statistics)
This paper investigates a generalization of Fisher’s entropy type information measure under the multivariate γ-order normal distribution, related to his measure, as well as its corresponding Shannon entropy. Certain boundaries of this information measure are also proved and discussed.